THE IDENTIFICATION ALGORITHM OF METROLOGICAL CHARACTERISTICS OF WIDE-RANGE PHOTOVOLTAIC SEMICONDUCTOR CONVERTERS WITH MULTIPLY IMPURITIES - O. K. Gusev; A. I. Svistun; L. I. Shadurskaya; N. V. Yarjembitskaya (Приборы и методы измерений)
Metrological features of photovoltaic semiconductor converters (PSC) based on semiconductors with the multiple-charge impurities are investigated in a wide range of power densities of optical radiation. The algorithm of the measurement procedure of the metrological characteristics of PSC is introduced not only at low densities of optical power, but at high, taking into account the boundary of nonlinear recombination. The estimation of accuracy of feature finding of the metrological characteristics PSC based on semiconductors with the multiple-charge impurities, is carried out, taking into consideration the area of nonlinear recombination.